Social media and social capital as risk of voluntary counseling and testing for human immunodeficiency virus - Qurniyawati, Eny; Sari, Jayanti Dian Eka; Fadhillah, Farah; Yuvianti, Yeshita Alifia; Kartika, Prima; Nasr, Nayla Mohamed Gomaa (Intelektual Pustaka Media Utama, 2025)
Teenagers are more susceptible to contracting human immunodeficiency virus (HIV). Of the 34 provinces in Indonesia, East Java continues to have the highest rate of new HIV diagnoses. One tactic for HIV prevention and control is voluntary counseling and testing (VCT). The purpose of this study is to examine the risk factors associated with the uptake of VCT for HIV among adolescents in the general population of East Java. A cross-sectional study design, a quantitative technique, and an observational methodology are all used in this research. 329 individuals in total, selected at random, took part in this study. The prevalence ratio (PR) with a 95% confidence interval was examined in order to determine the level of risk. Out of all the parameters that were found, social media access (PR = 10.133; 95%CI 1.293 - 79.422) and social capital (PR = 10.741; 95% 3.240 - 35.601) were found to have a substantial impact on VCT for HIV. Thus, it's critical to enhance social capital and implement educational initiatives on VCT for HIV using social media in order to improve teenagers' favorable perceptions of the treatment.